2012
DOI: 10.12968/ijtr.2012.19.5.288
|View full text |Cite
|
Sign up to set email alerts
|

‘I know how to look after myself a lot better now’: service user perspectives on mental health in-patient rehabilitation

Abstract: Aims: This research explored experiences of an in-patient mental health rehabilitation unit. This setting has a place in current services but has not been the focus for recent developments. Perspectives were sought from people who had been discharged more than a year previously. Method: A qualitative method was used. Ten service users were interviewed individually, using photographs of the unit to elicit responses. The data were subject to detailed analysis. Findings: Of the three overarching themes, the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous research has shown that predictability and the ability to control various environmental aspects are required to avoid the experience of deprivation, loss of control and feelings of helplessness (Evans, 2003;Huey & McNulty, 2005;Notley et al, 2012;Svensson, 2010)-experiences that may also increase the risk of suicide (Huey & McNulty, 2005). Moreover, the opportunity to regulate social interaction through access to private areas and the opportunity to choose levels of interaction could influence mental health and create sustainable recovery over time (Evans, 2003;Notley et al, 2012). The reinforcement of social exclusion by socio-spatial control mechanisms, such as rules, regulations and spatial attributes, not only creates feelings of loss of control but also generates a view of the adolescents as (potential) perpetrators, which in turn also risks amplifying the image of the adolescents as problematic in their own eyes (Kitsuse, 1962;Loseke, 2001;Ugelvik, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that predictability and the ability to control various environmental aspects are required to avoid the experience of deprivation, loss of control and feelings of helplessness (Evans, 2003;Huey & McNulty, 2005;Notley et al, 2012;Svensson, 2010)-experiences that may also increase the risk of suicide (Huey & McNulty, 2005). Moreover, the opportunity to regulate social interaction through access to private areas and the opportunity to choose levels of interaction could influence mental health and create sustainable recovery over time (Evans, 2003;Notley et al, 2012). The reinforcement of social exclusion by socio-spatial control mechanisms, such as rules, regulations and spatial attributes, not only creates feelings of loss of control but also generates a view of the adolescents as (potential) perpetrators, which in turn also risks amplifying the image of the adolescents as problematic in their own eyes (Kitsuse, 1962;Loseke, 2001;Ugelvik, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Using Photovoice can capture experiences beyond words and so is increasingly used in health research (Lal et al., 2012). Locally, the research partnership had previous experience of using photo-elicitation (Notley et al., 2013) and Photovoice (Bryant et al., 2011). It was agreed the latter would be more effective in achieving the study aim, as Photovoice has the potential for users to create cohesive and powerful representations.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of a research programme that was co-ordinated by a partnership of academics, service users and occupational therapists (Bryant et al., 2011; Makdisi et al., 2013; Notley et al., 2013). Research preceding this study (Bryant et al., 2016) offered insights into what service users valued about occupational therapy during an admission to an acute inpatient mental health unit.…”
Section: Introductionmentioning
confidence: 99%
“…The project design evolved so that current and recent service users of the hostel participated in photo-elicitation interviews (Notley et al 2012). The project recommendations were used to structure a staff review day, agreeing on how to refocus on individualising rehabilitation programmes.…”
Section: Service Users Photovoicementioning
confidence: 99%